DIPLOMASI INTERNASIONAL KIAI: Otonom dan Termobilisasi ? - Purwono, Andi; Hartati, Anna Yulia (Interdependence Journal of International Studies, 2026)
The participation of religious actors in diplomacy has been widely discussed in existing literature. Nevertheless, little attention has been paid to the question of the independence of their diplomacy in relation to state foreign policy. This article aims to describe the participation of kiai’s diplomacy as religious actors in relation to state diplomacy. This study employs a qualitative descriptive research design based on documentation analysis of relevant sources. The findings indicate evidence of diplomatic participation that is both autonomous and mobilized or invited by the state. Another finding reveals an intersection between the ideational interests of religious actors and the instrumental interests of the state. In this context, the diplomacy of religious actors within the political system input arena can function both as a source of demand and as a form of support. In the sphere of foreign policy implementation, the diplomacy of kiai can even become a determining factor in the success of government diplomacy.